DNA polygonal cavities with tunable shapes and sizes. Issue 90 (24th September 2015) - Sun, Sha; Wang, Mingyang; Zhang, Feifei; Zhu, Jin
Abstract : A new and simple angle control strategy to construct shape- and size-tunable DNA polygonal cavities was developed. Abstract : We developed a new and simple angle control strategy to construct shape- and size-tunable DNA polygonal cavities. A monomer with a controlled slope on one end was used for hierarchical assembly into diverse polygons in a single step. Additionally, by simply moving the position of sticky ends on the monomer, the cavity size can be precisely programmed.